Increased nitric oxide plasma concentration in dogs with naturally acquired chronic renal disease - Galvão, André B. [UNESP]; Carvalho, Marileda B. [UNESP]; Batalhão, Luciane G. [UNESP]; Silva, Juliana C.B.; Batalhão, Marcelo; Carnio, Evelin C. (FapUNIFESP (SciELO), 2017)
This study aimed to determine the amount of plasma nitric oxide in clinically stable dogs at different stages of chronic kidney disease (CKD). Five groups of dogs were studied, aged from 4 to 18, comprising of a control group composed of healthy animals (control n=17), group CKD stage 1 (DRC-1, n=12), group CKD stage 2 (CKD-2, n=10) group, CKD stages 3 (CRD-3, n=13) and Group CKD stage 4 (DRC-4, n=10). Dogs with CKD were clinically stable and received no treatment. Two blood samples were collected at 24 hours intervals (repeated measures) to obtain serum and plasma. The serum creatinine values were used to classify dogs as CG, CKD-1, CKD-2, CKD-3 and CKD-4, and were (1.02±0.02mg/dL), (1.07±0.04mg/dL), (1.81±0.03mg/dL), (3.40±0.15mg/dL) and (6.00±0.20mg/dL) respectively. The determination of nitric oxide (NO) was performed by dosing nitrate/nitrite indirectly, and used for measurement of nitrate according to the NO/ozone chemiluminescence. The data were submitted to ANOVA for nonparametric analysis(Kruskal-Wallis) (P < 0.05). The concentration of plasmatic NO did not differ significantly among GC (10.81±0.51μM), CKD-1 (15.49±1.97μM) and CKD-2 (19.83±3.31μM) groups. The plasma concentration of CKD-3 (17.02±1.73μM) and CKD-4 (83.56±13.63μM) was significantly higher compared with healthy dogs. In conclusion, the NO plasma concentration can increase in dogs with CKD and become significantly higher in stage 3 and 4 dogs.
Keywords: Azotemia; Chronic renal disease; Creatinine; Dog; Hypertension; Nitric oxide plasma concentration; Proteinuria